Menakar Kesehatan Bank: Dampak Kecukupan Modal, Likuiditas, dan Resiko Kredit terhadap Profitabilitas - Putri Yulianti; Irvan Yoga Pardistya; Nurul Amalia Ramdan (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2026)
This study aims to determine the Measuring of Bank Health: The Impact of Capital Adequacy, Liquidity, and Credit Risk on Profitability in Digital Service Banks listed on the Indonesia Stock Exchange during the period 2020-2024. This study uses a descriptive quantitative method with secondary data and multiple linear regression analysis using SPSS version 23 software. The sample selection was carried out by purposive sampling, resulting in 14 companies as samples. The results show that CAR and NPL have a significant negative effect on ROE, while LDR does not have a partial significant effect on ROE with a significance value of 0.05. Simultaneously, this independent variable has a significant effect on ROE with a significance value of 0.000, and has an influence of 41.7% according to the R Square value. Based on these findings, it is recommended that digital bank management maintain a balance between capital adequacy and credit provision and reduce the ratio of non-performing loans so that the company's financial performance can be optimized sustainably.